2020
DOI: 10.1101/2020.11.05.370585
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

In vivoproteomic mapping through GFP-directed proximity-dependent biotin labelling in zebrafish

Abstract: Protein interaction networks are crucial for complex cellular processes. However, the elucidation of protein interactions occurring within highly specialised cells and tissues is challenging. Here we describe the development, and application, of a new method for proximity-dependent biotin labelling in whole zebrafish. Using a conditionally stabilised GFP-binding nanobody to target a biotin ligase to GFP-labelled proteins of interest, we show tissue-specific proteomic profiling using existing GFP-tagged transge… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 53 publications
1
12
0
Order By: Relevance
“…Importantly, we identified SSX2IP using both BirA-GBP/GFP-WtipN and WtipN-BirA, increasing our confidence in the result. Thus, our findings and a similar report using zebrafish embryos (Xiong et al, 2021) indicate that TPB represents a versatile approach for protein interaction studies of various GFP-tagged proteins.…”
Section: Discussionsupporting
confidence: 84%
“…Importantly, we identified SSX2IP using both BirA-GBP/GFP-WtipN and WtipN-BirA, increasing our confidence in the result. Thus, our findings and a similar report using zebrafish embryos (Xiong et al, 2021) indicate that TPB represents a versatile approach for protein interaction studies of various GFP-tagged proteins.…”
Section: Discussionsupporting
confidence: 84%
“…Xiong et al (32) used a conditionally stabilized GFP-nanobody fused to TurboID to target proximal labeling to GFP tagged proteins in muscle, while Pronobis et al (26) used BioID2 targeted cardiomyocytes to investigate proteome changes during cardiac regeneration in adult fish. Both these studies showed promise for investigating proximal interactors in vivo in the zebrafish, and the Xiong et al, manuscript is particularly interesting in that it permits use of existing green fluorescent protein fusion transgenics directly after a cross with a universal GFP-nanobody expressing line (32). Our manuscript differs from these two studies in a number of ways.…”
Section: Discussionmentioning
confidence: 96%
“…The generation of molecularly evolved variants of the E. coli BirA enzyme, called TurboID and miniTurbo, that display 15 to 30 times the labeling efficiency of BirA* has been a major breakthrough in enabling more efficient proximity-dependent biotinylation in different in vivo models, including C. elegans (9), D. melanogaster (9,27), A. thaliana (28), N. benthamiana (28,29), S. pombe (30), and M. musculus (31). Using transgenics in zebrafish, Xiong et al recently demonstrated the applicability TurboID through the fusion of a GFP nanobody to TurboID: crosses to transgenic lines expressing fusions of proteins of interest to the Clover green fluorescent protein enabled labeling and recovery of proximal interactors to cavin proteins (32). Yet, proximity-dependent biotinylation approaches are still in their infancy, and more thorough optimization and benchmarking of the approaches is needed; it has also not been clearly determined whether the more rapid and scalable mRNA injection systems lead to high-quality proximal proteomes.…”
Section: Introductionmentioning
confidence: 99%
“…Two recent publications have already demonstrated the use of proximity-dependent labeling in zebrafish. Xiong et al (32) used a conditionally stabilized GFP-nanobody fused to TurboID to target proximal labeling to GFP tagged proteins in muscle, while Pronobis et al (26) used BioID2 targeted cardiomyocytes to investigate proteome changes during cardiac regeneration in adult fish. Both these studies showed promise for investigating proximal interactors in vivo in the zebrafish, and the Xiong et al, manuscript is particularly interesting in that it permits use of existing green fluorescent protein fusion transgenics directly after a cross with a universal GFP-nanobody expressing line (32).…”
Section: Discussionmentioning
confidence: 99%
“…The generation of molecularly evolved variants of the E. coli BirA enzyme, called TurboID and miniTurbo, that display 15 to 30 times the labeling efficiency of BirA* has been a major breakthrough in enabling more efficient proximity-dependent biotinylation in different in vivo models, including C. elegans (9), D. melanogaster (9, 27), A. thaliana (28), N. benthamiana (28,29), S. pombe (30), and M. musculus (31). Using transgenics in zebrafish, Xiong et al recently demonstrated the applicability TurboID through the fusion of a GFP nanobody to TurboID: crosses to transgenic lines expressing fusions of proteins of interest to the Clover green fluorescent protein enabled labeling and recovery of proximal interactors to cavin proteins (32). Yet, proximity-dependent biotinylation approaches are still in their infancy, and more thorough optimization and benchmarking of the approaches is needed; it has also not been clearly determined whether the more rapid and scalable mRNA injection systems lead to high-quality proximal proteomes.…”
Section: Introductionmentioning
confidence: 99%